Are non-farming consumers willing to pay "a good market price" for iron-biofortified finger millet? Evidence from experimental auctions in Karnataka, India. Issue 5 (3rd July 2020) - Meier, Claudia; El Benni, Nadja; Sakamma, Srinivasaiah; Moakes, Simon; Grovermann, Christian; Quiédeville, Sylvain; Stolz, Hanna; Stolze, Matthias; Umesh, K. Basegowda
Abstract : Purpose: Biofortification of staple crops is a promising strategy to alleviate micronutrient deficiencies in rural populations of the developing world. The possibility to sell biofortified crops at "a good market price" plays a vital role for the acceptance by smallholder farmers. This study is therefore focused on non-farming consumers' willingness to pay (WTP) for biofortified crops. Design/methodology/approach: Specifically, we elicited non-farming consumers' WTP a premium for the improved iron content (+30% iron) in a 1kg finger millet bag using a 2nd price Vickrey auction with six auction rounds and one health- and one process-related information treatment. Due to multiple bids per subject, premiums were analyzed using a linear mixed-effects model, controlling for market feedback and auction round. Findings: Despite more than half of the respondents being skeptical toward new crop varieties, the acceptance rate was very high (98% with a WTP above zero). The average premium amounted to 27% and could be significantly increased with the provision of health-related information. In contrast, information about the breeding method was ineffective. The WTP was significantly higher for higher income and lower for higher age, education and skepticism toward new crop varieties and increased with increasing rounds. Research limitations/implications: Our results suggest that non-farming consumers are willing to pay "a good market price" for iron-biofortified finger millet. Our analysis also confirms the importance of health-related information for raising consumers' WTP. This information supports the further development and introduction of biofortified crops to alleviate micronutrient malnutrition. Originality/value: This study adds to the still limited literature on consumers' WTP for iron-biofortified crops in India, focusing on non-farming consumers to assess the price such crops can achieve on the market.